Penerapan model pembelajaran kooperatif tipe examples non examples berbantuan media gambar untuk meningkatkan hasil belajar geografi - I Dewa Made Nariana (Indonesian Journal of Educational Development, 2020)
The non-examples examples learning model is a type of learning that activates students by means of the teacher attaching examples of pictures that fit the learning objectives. This study aims to determine (1) Improving student learning outcomes; (2) Teacher and student activities; (3) Teacher skills in managing learning; and (4) Student responses to the examples non examples learning model. The subjects in this study were students of class X IPS1 SMA Negeri 1 Marga academic year 2018/2019. The object of this research was 31 students of class X IPS1 SMA Negeri 1 Marga. Data collection is done by using (1) Question sheets; (2) Observation sheet of teacher and student activities; (3) Teacher skills observation sheet; and (4) Student response sheets. Data analysis uses descriptive statistics of percentages. The results showed that the percentage of individual completeness in the first cycle was 68%, in the second cycle 74% and in the third cycle 93%.Classical completeness in the first cycle is 60%, in the second cycle 70% and in the third cycle 90%, the activities of teachers and students from cycle I, II to cycle III have changed better and have been categorized according to established time standards. Teacher skills in managing learning in the first cycle scored 2.7 in the good category, in the second cycle the score was 2.8 in the good category and in the third cycle it was 2.9 in the good category. Student responses to the examplesnon examples learning model, which is 86% of 31 students think that by learning through the examples non examples learning model assisted by the media images can understand the subject matter they have followed. Model pembelajaran examples non examples merupakan tipe pembelajaran yang mengaktifkan peserta didik dengan cara guru menempelkan contoh gambar-gambar yang sesuai dengan tujuan pembelajaran. Penelitian ini bertujuan untuk mengetahui (1) Peningkatan hasil belajar siswa; (2) Aktivitas guru dan siswa; (3) Keterampilan guru dalam mengelola pembelajaran; dan (4) Respon siswa terhadap model pembelajaran examples non examples. Subjek dalam penelitian ini adalah siswa kelas X IPS1 SMA Negeri 1 Marga Tahun Pelajaran 2018/2019. Objek dalam penelitian ini adalah siswa kelas X IPS1 SMA Negeri 1Marga. Pengumpulan data dilakukan dengan menggunakan (1) Lembar soal; (2) Lembar pengamatan aktivitas guru dan siswa; (3) Lembar pengamatan keterampilan guru; dan (4) Lembar respon siswa. Analisis data menggunakan statistik deskriptif %tase. Hasil penelitian menunjukkan bahwa %tase ketuntasan individual pada siklus pertama 68%, pada siklus kedua 74% dan pada siklus ketiga 93%. Ketuntasan klasikal pada siklus pertama 60%, pada siklus kedua 70% dan pada siklus ketiga 90%, aktivitas guru dan siswa dari siklus I, II sampai siklus III telah terjadi perubahan lebih baik dan sudah dikategorikan sesuai dengan standarwaktu yang ditetapkan. Keterampilan guru dalam mengelola pembelajaran pada siklus pertama memperoleh skor 2,7 dengan kategori baik, pada siklus kedua memperoleh skor 2,8 dengan kategori baik dan pada siklus ketiga menjadi 2,9 dengan kategori baik. Respon siswa terhadap model pembelajaran examples non examples, yaitu 86% dari 31 siswa berpendapat bahwa dengan belajar melalui model pembelajaran examples non examples berbantuan media gambar dapat memahami materi pelajaran yang telah mereka ikuti.